Pastoral power manifestations within the guidance professionals' talk on guidance practices - Samira Harjula; Mira Kalalahti (Taylor & Francis Group, 2024)
ABSTRACTYoung people in the Nordic countries have many options and face obligations to participate in career guidance and counselling (guidance). In Finland, young people are subjected to multiple institutionalized guidance practices especially in educational transition phases. Guidance has various objectives as a public policy, thereby setting a framework for guidance professionals too. By using Foucault's conceptualization on 'pastoral' power, we studied how guidance professionals ('shepherds') guide young people ('the flock') towards 'wellbeing'. Our aim was to analyse how pastoral power is manifested in guidance practices by asking what governmental discourses the guidance professionals refer to when talking about guidance and how these discourses are practiced in guidance. Our data comprise Finnish guidance professionals' interviews (n = 15). As a result, dominant governmental discourses of employability, economic efficiency and lifelong learning were identified. Guidance involved pastoral power and demanded employability and educability for the young. Guidance professionals have a crucial role in implementing governmental discourses into guidance practices. These practices create a narrow perspective for young people and guidance professionals, who are simultaneously the mediators and targets of governmental power.